Dose reconstruction technique using non-rigid registration to evaluate spatial correspondence between high-dose region and late radiation toxicity: a case of tracheobronchial stenosis after external beam radiotherapy combined with endotracheal brachytherapy for tracheal cancer - Kobayashi, Kazuma; Murakami, Naoya; Inaba, Koji; Wakita, Akihisa; Nakamura, Satoshi; Okamoto, Hiroyuki; Sato, Jun; Umezawa, Rei; Takahashi, Kana; Igaki, Hiroshi; Ito, Yoshinori; Shigematsu, Naoyuki; et al. (Journal of Contemporary Brachytherapy, 2016)
Purpose : Small organ subvolume irradiated by a high-dose has been emphasized to be associated with late complication after radiotherapy. Here, we demonstrate a potential use of surface-based, non-rigid registration to investigate how high-dose volume topographically correlates with the location of late radiation morbidity in a case of tracheobronchial radiation stenosis. Material and methods: An algorithm of point set registration was implemented to handle non-rigid registration between contour points on the organ surfaces. The framework estimated the global correspondence between the dose distribution and the varying anatomical structure. We applied it to an 80-year-old man who developed tracheobronchial stenosis 2 years after high-dose-rate endobronchial brachytherapy (HDR-EBT) (24 Gy in 6 Gy fractions) and external beam radiotherapy (EBRT) (40 Gy in 2 Gy fractions) for early-stage tracheal cancer. Results and conclusions : Based on the transformation function computed by the non-rigid registration, irradiated dose distribution was reconstructed on the surface of post-treatment tracheobronchial stenosis. For expressing the equivalent dose in a fractional dose of 2 Gy in HDR-EBT, α/β of linear quadratic model was assumed as 3 Gy for the tracheal bronchus. The tracheobronchial surface irradiated by more than 100 Gy3 tended to develop severe stenosis, which attributed to a more than 50% decrease in the luminal area. The proposed dose reconstruction technique can be a powerful tool to predict late radiation toxicity with spatial consideration.